A model of an inflammatory bowel disease population-based registry: The Forlì experience (1993–2013). Issue 1 (January 2018) - Valpiani, Daniela; Manzi, Ilaria; Mercuriali, Marina; Giuliani, Orietta; Ravaioli, Alessandra; Colamartini, Americo; Bucchi, Lauro; Falcini, Fabio; Ricci, Enrico
Abstract: Background and aims: The article presents a population-based registry designed to estimate incidence and prevalence of inflammatory bowel disease (IBD) in the area of Forlì (north-eastern Italy). Methods: The registry included all patients with IBD ulcerative colitis (UC) and Crohn's disease (CD) in the Forlì area from 1993 to 2013. A data manager matched records from various sources. Results: Seven hundred ninety-one patients were registered during the study period, 564 (71.3%) with UC and 227 (28.7%) with CD. The standardized annual incidence rate for UC was 12.8 per 100, 000 females (95% CI 11.1–14.4) and 15.7 per 100, 000 males (95% CI 13.9–17.5). That of CD was 7.0 per 100, 000 for females (95% CI 5.7–8.3) and 5.4 per 100, 000 males (95% CI 4.3–6.4). The prevalence of CD and UC on 1 January 2014 was 109.2 per 100, 000 inhabitants (95% CI 94.3–124.2) and 266.4 per 100, 000 inhabitants (95% CI 243.4–289.7), respectively. Conclusions: Although further studies are needed, the data suggest that incidence and prevalence of IBD in Italy are underestimated.